Design and Analysis of Human Resource Development Strategies in Remote Work Conditions: An Applied Study in the Iraqi Ministry of Planning - Salman Al-Tamimi, Mostafa Hussain; Eslami, Ghasem; Farahi , Mohammad Mahdi; Rahimnia, Fariborz (AI and Tech in Behavioral and Social Sciences, 2026)
With the growing expansion of remote work and the transformation of workplace structures, organizations—particularly in the public sector—have encountered new challenges in the field of human resource development. This transformation requires the redesign of strategies tailored to technology-driven, non-face-to-face work environments. The purpose of this study is to identify and analyze effective human resource development strategies under remote work conditions, with a focus on the operational context of the Iraqi Ministry of Planning. This study employed a mixed-methods approach (qualitative–quantitative) and was conducted in three stages. In the first stage, through a systematic review of the scientific literature, 33 initial strategies were collected. Subsequently, by implementing two rounds of the Delphi method with the participation of 14 experts, the final list of 29 strategies was extracted. In the third stage, exploratory factor analysis was applied to identify the conceptual dimensions of the strategies, resulting in three main axes: “individual and professional empowerment,” “team and organizational cultural development,” and “digital transformation of human resources.” The findings revealed that human resource development in the context of remote work requires a comprehensive, technology-oriented, and flexible perspective that must align with the characteristics of virtual work environments and the requirements of public organizations. Furthermore, recommendations were provided for designing blended training programs, strengthening virtual interactions, and enhancing employees’ technological empowerment. By localizing global approaches within Iraq’s administrative structures, this study has taken an innovative step toward formulating human resource development policies under remote work conditions.